NICER, NuSTAR, and Insight-HXMT Views to Black Hole X-Ray Binary SLX 1746–331 - Peng, Jing-Qiang; Zhang, Shu; Shui, Qing-Cang; Zhang, Shuang-Nan; Chen, Yu-Peng; Kong, Ling-Da; Yu, Zhuo-Li; Ji, Long; Wang, Peng-Ju; Ge, Ming-Yu; Qu, Jin-Lu; Tao, Lian; et al. (Astrophysical journal. Letters, 2024)
We study the spectral and temporal properties of the black hole (BH) X-ray transient binary SLX 1746–331 during the 2023 outburst with NICER, NuSTAR, and Insight-HXMT observations. Through the joint fitting of the spectra from NICER, NuSTAR, and Insight-HXMT, the spin and inclination angles are measured for the first time as 0.85 ± 0.03 and 53° ± 0.°5, respectively. Accordingly, the mass of the compact star is updated from the previous lower limit of 3.3 ± 2.1 M ⊙ to 5.5 ± 3.6 M ⊙ , which is consistent with 5.2 ± 4.5 M ⊙ measured with an empirical mass–luminosity correlation of BH samples. With more NICER observations covering the later decay of the outburst, we confirm that the entire outburst was dominated by the disk emissions, and the thermal spectrum follows F ∝ T in 3.974 ± 0.003 , until a luminosity of over 2 magnitudes lower than the maximum of the outburst.